Modernity in Indian social theory - Raghuramaraju, A., 1957- (New Delhi ; Oxford : Oxford University Press, 2011)
This text deals with a re-reading of the concept of modernity in Indian social theory and its application to understand contemporary Indian society and texts. It examines the work of several past and contemporary thinkers as well as issues like nationalism, secularism, notions of majority and minority, and lived Dalit experiences.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social change -- India; India -- Social conditions -- 1947-; Civilization, Modern